Structural organization of a multi-level intelligent utility metering system with increased survivability - I. A. Magomedov; A. I. Magomedov; M. N. Khidivov; M. Sh. Usmanov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. Development of principles for constructing a multi-level intelligent utility metering system (MISUKU) with increased survivability based on modern utility metering devices (CU) with expanded communication and functionality, as well as determining the fundamental possibility of constructing MISUKU based on a self-configuring mesh network of utility metering devices.Method. The study is based on an analysis of the functional and communication capabilities of modern utility metering devices and advances in the field of information technology and computer technology, as well as the availability of hardware for organizing inexpensive wireless data transmission lines. The work outlines the basic principles for constructing self-adjusting mesh networks of digital metering devices, while the basic device of the first-level system is a subscriber electric energy meter (ASEM), which has good energy, communication and functional parameters.Result. The basic principles for the creation of SNF utility metering devices and the structure of a multi-level system have been developed: the first level consists of ASEE with subscriber gas and water metering devices with built-in electronic devices connected to it via a radio channel; the second level is the district's strategic nuclear forces with a network coordinator installed at the district's transformer substation or on the roof of a high-rise apartment building. The third level consists of microdistricts united in the strategic nuclear forces system in the center, of which there is a control center for collecting and processing accounting and service information, as well as a payment center.Conclusion. The use of ASEE with mechanical gas and water meters and built-in electronic set-top boxes connected to it via a radio channel will make it possible to build a node of a self-organizing mesh network (SNF) of the first level, and on the basis of this network to create a MISUKU with high communication characteristics. The MISUKU structures presented in the work with increased survivability based on intelligent mesh networks of utility metering devices make it possible to increase the reliability of accounting information and the reliability of communications.